Philosophy for beginners - Osborne, Richard, 1952-; Edney, Ralph (New York. Writers and Readers Publishing, Incorporated., 1992)
Why does philosophy give some people a headache, others a real buzz, and yet others a feeling that it is subversive and dangerous? Why do a lot of people think philosophy is totally irrelevant? What is philosophy anyway? The ABCs of philosophy - easy to understand but never simplistic. Beginning with basic questions posed by the ancient Greeks - "What is the world made of?" "What is man?" "What is knowledge?" "What is good and evil?"--This guide traces the development of these questions as the key to understanding how western philosophy developed over the last 2,500 years
What is philosophy? -- Greece -- Rome -- Early Christianity -- Medieval religious philosophy -- The Renaissance -- Reformation and Counter Reformation -- Enlightenment -- Idealism -- Romantic reaction -- Materialism -- Sui generis -- Utilitarianism -- Positivism -- Eclecticism -- American philosophy -- The irrational -- Logic -- Language -- Phenomenology and existentialism -- Marxists -- Linguistics, semiology, structuralism
Includes bibliographical references (pages 183-184) and index
Keywords: Philosophy; Philosophy -- Comic books, strips, etc; Comics (Graphic works)